The Effect Of Online Learning On Academic Interest Of Evangelical Teological Seminary Of Indonesia - Surabaya - Christian Melkianus Boka; Lilis Setyarini; Willopo Koeswardoyo (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2021)
Interest in learning is an interest in a lesson and encourages individuals to learn and pursue the lesson, Interest in learning is an actualized desire or intention to be involved in certain learning activities while online learning is a learning process with the help of information and communication technology which is done online or virtual with not face to face. The online learning process carried out during the COVID-19 pandemic has had a major impact on education. This study aims to determine whether there is an effect of online learning on student interest in Evangelical Theological Seminary of Indonesia - Surabaya. The research method used in this research is a quantitative research design with a survey method. Characteristics of respondents from 166 respondents who were the student population of Evangelical Theological Seminary of Indonesia – Surabaya studied consisted of age, education, and domicile. The contribution of the online learning variable in shaping the student's learning interest variable at Evangelical Theological Seminary of Indonesia – Surabaya is 55.6%, the researcher argues that online learning is effective for continuous use and becomes a learning system that complements the traditional learning process.